2D petroleum system analysis of the Tarfaya Basin, on-offshore Morocco, North Africa - Sachse, Victoria F.; Wenke, Axel Adrian Oliver; Littke, Ralf; Jabour, Haddou; Kluth, Oliver; Zühlke, Rainer (Marine and petroleum geology, 2016)
This study presents a 2D basin model along a transect crossing the on- and offshore Tarfaya Basin, Morocco, in SE-NW direction. The aim of the project is to investigate the thermal evolution of the basin fill and its influence on the petroleum system.
Gesehen am 07.05.2020